The Suitability Of The Educandy Studio App To Improve Students'senior High School Grammar Achievement - Nerin Pratiwi; Dian Fadhilawati (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
The study aimed to evaluate how effectively the Educandy Studio Application works to improve grammatical knowledge of senior high school students, particularly focusing on the simple past tense within the context of Narrative Text. Employing a pre-experimental one-group pre-test and post-test design, the impact of the application on the grammar achievement of tenth-grade pupils at SMAN 1 Kesamben Blitar in classes X–H was examined. The research procedure consisted of pre-tests, application of the treatment, and post-tests, with data gathered through test administration. A trial test was conducted to ensure validity and reliability. Results revealed a significant enhancement in students' grammar proficiency in narrative text, with scores rising from 71.87 in the pre-test to 81.90 once the Educandy Studio program was put into use. The statistical examination employing paired sampled T-tests verified a substantial variance between the data collected before and after the intervention (Level of significance < 0.05). These results imply that the implementation of Educandy Studio successfully improved grammar attainment within the narrative text at SMAN 1 Kesamben Blitar. The study recommends integrating the Educandy Studio Application into English teaching, encouraging students to explore its use across subjects. Subsequent studies ought to investigate the feedback from students and teachers and conduct comparisons with similar applications to ascertain the most appropriate resources for improving grammar proficiency in English classrooms.